The Impact of Double Consciousness on The Mental Health of Black People in The United States. Case Study: The Souls of Black People by W.E.B. Du Bois - Lamouri, Lydia; Aribi, Ibrahim (Faculty of Letters and Foreign Languages Department of English, 2023)
This research study examines W.E.B. Du Bois' idea of double consciousness from his book "The Souls of Black Folk."(1903) . This study focuses on the negative impact of double consciousness on the mental health of black people in the United States. There are many causes or factors that help to emerge the idea of double consciousness, such as racism, inequality, race, color line, and discrimination. The importance of education and the role of the family in addressing this issue for building a confident society to face different inhumanity practices. Many black African American writers, such as Frantz Fanon, Toni Morisson, and Ralph Ellison, use the idea of double consciousness, and this research study will discuss the different subtleties of "double consciousness" in their works. I selected The Souls OF Black Folk (1903) by W.E.B. DuBois to examine the idea of double consciousness and its negative effects on the mental health of black people from psychological and physical violence, as well as how the view of white people can affect the personality of African Americans